Some Element Levels in Moss Samples Collected from the Igdir-Nahhicevan International Highway, Turkey - Ozdemir, Turan; Batan, Nevzat; Mendil, Durali; Apaydin, Gokhan; Cengiz, Erhan (Asian Journal of Chemistry, 2013)
Twenty-six moss and seven soil samples were collected from near the Igdir- Nahhichevan international highway in Turkey. Seventeen elements (Na, Mg, Al, Si, P, S, K, Ca, Ti, Fe, Cu, Zn, Sr, Cr, Mn, Rb and Pb) were analyzed using X-ray fluorescence spectrometry. The element concentrations were found to be 1000-1862 μg/g (Na), 2174-6578 μg/g (Mg), 1308-30669 μg/g (Al), 11708-73710 μg/g (Si), 91-659 μg/g (P), 45-2680 μg/g (S), 1123-2667 μg/g (K), 5969-13997 μg/g (Ca), 641-1387 μg/g (Ti), 5855-17133 μg/g (Fe), 23-36 μg/g (Cu), 10-93 μg/g (Zn), 29-114 μg/g (Sr), 4-85 μg/g (Cr), 17-326 μg/g (Mn), 6-19 μg/g (Rb), 1-14 μg/g (Pb) for mosses and 324254-402976 μg/g (Si), 35347-92506 μg/g (Na), 28261-76471 μg/g (Ca), 3822-72123 μg/g (Mg), 52731-66335 μg/g (Fe), 28115-39747 μg/g (Al), 9659-11664 μg/g (K), 6928-11617 μg/g (Ti), 936-1385 μg/g (S), 585 μg/g (P), 149-261 μg/g (Sr), 126 μg/g (Zn), 15-240 μg/g (Cr), 42-180 μg/g (Cu), 89 μg/g (Mn), 27-46 μg/g (Rb) and 37 μg/g (Pb) for soil, respectively.